Velutha: The Abject - Ghulam Mohammad, Shazia; ur Rahman, Atteq (The Journal of Humanities & Social Sciences, 2023)
Arundhati Roy situates the story of The God of Small Things in Ayemenem — a village in Kerala, in the south-west of India. It is a case study of Velutha, the untouchable whose very name smacks of loathing and nausea one feels at the mention of it let alone sight of him. By focusing on the cross-cultural caste system, Arundhati Roy takes up an issue of social, cultural and universal significance. It apparently deals with the identity of Velutha, a paravan, which is at stake. He is the one who is expected not to leave any footprints on the earth and any image in the mirror. His identity is an issue and at issue because social, cultural and “Love Laws” (33) 2 do not favour him or acknowledge his right to be. A closer analysis of the novel directs the reader’s mind to a series of underlying ‘lacks’ or voids at the core of formation of his subjectivity. The society constitutes a body from which Velutha is excluded as an undesirable or unhygienic element; he is objectified to which he retaliates. He seeks unconscious identification with the system from which he is expelled. .If Velutha is neither a subject nor an object then what is he? Who is he? This study provides a valid ground that Velutha does not qualify for both. Velutha’s dilemma can be better understood if he is placed on the borderline of subject-object distinction3. This study takes him as a specimen for analysis and examines his borderline position from the viewpoint of Julia Kristeva’s concept of abjection. A psychoanalytical framework facilitates the reader to determine his position.